An Acute Disseminated Encephalomyelitis‐Like Illness in the Elderly: Neuroimaging and Neuropathology Findings. Issue 3 (29th November 2016) - Kaunzner, Ulrike W.; Salamon, Elliott; Pentsova, Elena; Rosenblum, Marc; Karimi, Sasan; Nealon, Nancy; Lavi, Ehud; Jamieson, Dara G.
ABSTRACT: INTRODUCTION: Acute disseminated encephalomyelitis (ADEM) is a rare demyelinating disease of the central nervous system (CNS) that classically occurs in children and adolescents. It characteristically presents with acute inflammation, resulting in demyelination, often following an infectious disease. ADEM has been described in adult patients, but the incidence in the adult and especially elderly population is low. CASES: We describe five older adults (age 57 to 85) who presented with acute neurological symptoms. Three patients presented with an infectious illness preceding the event, 4 patients were encephalopathic, and oligoclonal bands (OCBs) were negative in all tested cases. The clinical scenario and imaging studies suggested alternative diagnoses, such as metastasis, primary CNS tumor, or stroke. Two patients had contrast enhancing lesions, two other patients had lesions with restricted diffusion on diffusion‐weighted imaging. Neuropathologic diagnostic from biopsy or autopsy was eventually conclusive, showing perivascular zones of myelin loss with relative axonal sparing in all five cases. CONCLUSION: Each of these patients was found to have pathological findings of acute demyelination on tissue diagnosis, suggesting ADEM or ADEM‐like disease. The initial presentation and imaging was pointing toward other diagnoses. Broad differential diagnosis is important, especially for older patients, and pathological proof might be warranted for a conclusive diagnosis.